2013
DOI: 10.5811/westjem.2013.5.16215
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Noise by Emergency Department Nurses

Abstract: Introduction:Noise in the emergency department (ED) may be perceived to be high by both patients and nurses alike. This increased noise level is hypothesized to be responsible for communication interference and subsequent disruption of complex procedures and decision-making. The objective of this study is to quantify ambient noise level in an ED while obtaining coincident subjective surveys from nurses in the assessment of actual versus perceived noise.Methods:Data collected from surveys of ED nurses on each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Indeed, other studies in hospital context found similar data [1,29,30]. However, in a study conducted in an emergency department, 53% of the sample (only constituted by nurses) felt their cognitive function was never or rarely affected by noise [31]. The morning shift was perceived as the most annoying, followed by night shift.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, other studies in hospital context found similar data [1,29,30]. However, in a study conducted in an emergency department, 53% of the sample (only constituted by nurses) felt their cognitive function was never or rarely affected by noise [31]. The morning shift was perceived as the most annoying, followed by night shift.…”
Section: Discussionmentioning
confidence: 53%
“…The body's response in the form of fever at the time of infection is usually beneficial, because the immunological mechanism will be accelerated. An increase in body temperature will also harm some microorganisms, but if the febrile condition is maintained for a long time, it will have a detrimental impact (Graneto, 2010;Batchelor et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…56 An additional survey conducted in the US by Graneto and Damm determined that ED nurses did not seem to be troubled by routine noise levels in the ED although the effect on other professional groups and patients was not explored. 57 High workload intensity and overcrowding is synonymous within many ED settings, and may adversely affect communication. The year-long qualitative observational study of patient-provider communication in the ED by Ekwall identified overcrowding as an obstacle to decision making during triage.…”
Section: Information Provisionmentioning
confidence: 99%